2015
DOI: 10.1080/10934529.2015.992684
|View full text |Cite
|
Sign up to set email alerts
|

Well water contamination in a rural community in southwestern Pennsylvania near unconventional shale gas extraction

Abstract: Reports of ground water contamination in a southwestern Pennsylvania community coincided with unconventional shale gas extraction activities that started late 2009. Residents participated in a survey and well water samples were collected and analyzed. Available pre-drill and post-drill water test results and legacy operations (e.g., gas and oil wells, coal mining) were reviewed. Fiftysix of the 143 respondents indicated changes in water quality or quantity while 63 respondents reported no issues. Color change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Environmental impacts of UOG exploration can be manifold , and concerns have focused on water contamination ( Jackson et al, 2013;Vengosh et al, 2014;Alawattegama et al, 2015) and air emissions (Field et al, 2014;Moore et al, 2014), which can come from various steps in the UOG exploration process, such as during the hydraulic fracturing backflow period. Atmospheric emissions are dominated by emissions of methane, the dominant component of natural gas and a strong greenhouse gas Elementa: Science of the Anthropocene ‱ 4: 000096 ‱ doi: 10.12952/journal.elementa.000096 (Brandt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental impacts of UOG exploration can be manifold , and concerns have focused on water contamination ( Jackson et al, 2013;Vengosh et al, 2014;Alawattegama et al, 2015) and air emissions (Field et al, 2014;Moore et al, 2014), which can come from various steps in the UOG exploration process, such as during the hydraulic fracturing backflow period. Atmospheric emissions are dominated by emissions of methane, the dominant component of natural gas and a strong greenhouse gas Elementa: Science of the Anthropocene ‱ 4: 000096 ‱ doi: 10.12952/journal.elementa.000096 (Brandt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The integrated framework representative of the multiobjective shale gas water management optimization model is presented based on a real-life scenario, hypothetical proposition, data, information, and a quick review of the published research (Lutz et al [12], Rahm and Riha [54], Rahm et al [55], Zhang et al [22], Alawattegama [56]). The unified optimal shale gas water planning model was structured to manifest the real-life scenario in the current and future characteristic features of shale gas extraction processes.…”
Section: A Computational Studymentioning
confidence: 99%
“…[22] Well completion records obtained from the PA DEP showed that one company reported using an average of 3.2 million gallons of fracking fluid and 300,000 lbs of proppant per well in wells drilled in Butler County, PA in 2008 to 2012. [23] The large number and size of the storage containers for the water, chemicals, and proppant, the mixers and pressure pump trucks, as well as the accommodations for control operations, require a well pad of sizable dimensions, often 3-7 acres (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%